THE REFLECTIONS OF THE MOTIFS AND SYMBOLS IN TURKISH MYTHOLOGY TO THE WORKS OF MEHMET SAĞ - Ali Ayhan GÜNEYSU (Fırat University, 2019)
All of the myths, legends, texts, belief systems, social life styles and intangible cultural values ??that make up the past of the societies are the images that reveal the traces and the position of that community within the universe. The myhs are the product of the common cultural heritage.'Mythology' is the name given to a branch of science that examines the legends of a particular tribe. The myths are the first source of the unique features of every nation's national ideology and national psychology. Therefore, the relations between cultures can be determined by mythologies. The mythology has a very significant part in the process of evolution from the day of human existence up to current time. These mythologies play a major role in the shaping of cultures within themselves as determinants of societies. As one of these mythologies, Turkish mythology have inspired many of our artists. The motifs and marks in the cultural values ??of Turkish society are reflected in the works of our artists. In this sense, our artists have created beautiful works in various fields. Mehmet Sağ is one of our artists who have extensively worked in the field of Turkish mythology. In his works, the artist depicted the motifs and symbols that show Turkish society has a deeply rooted past. In this work, our artist used the works of acrylic and watercolor techniques under the influence of how the Turkish societies perceived the universe. Moreover, he frequently made use of the mythological animals, motifs and symbols which relates to the Turkish belief system in some extent while also questioning natural events. He emphasized the colors in the Turkish mythology and added a mystical atmosphere to his works. We will investigate the mythological items, symbols and colors in Mehmet Sağ's works and present the results of our investigations .